Working towards equity : disability rights activism and employment in late twentieth-century Canada - Galer, Dustin, 1983- (University of Toronto Press, 2018)
In Working towards Equity, Dustin Galer argues that paid work significantly shaped the experience of disability during the late twentieth century.